Ефективність енергетичного розділення стиснутих природного газу і повітря - Кашина, Олена; Балінський, Іван (Видавництво Національного університету «Львівська політехніка», 2001)
Analytic dependence between values of effectiveness of energetic separation of compressed air and compressed natural gas for various pressure values, chemical consistency and correlations of the quantity heated and cool flows has been determined.